Multiple weak supramolecular interactions stabilize a surprisingly twisted As2L3 assembly - Pitt, Melanie A.; Zakharov, Lev N.; Vanka, Kumar; Thompson, Ward H.; Laird, Brian B.; Johnson, Darren W. (Chemical Communications, 2008)
A combined crystallographic, DFT and NMR spectroscopic study of a flexible As(2)(3) assembly reveals temperature dependent conformational behavior in solution and a highly asymmetric structure stabilized by As-pi and edge-to-face aromatic interactions.

Multipoint anchoring of the [2.2.2.2]metacyclophane motif to a gold surface via self-assembly: coordination chemistry of a cyclic tetraisocyanide revisited - Toriyama, Masaharu; Maher, Tiffany R.; Holovics, Thomas C.; Vanka, Kumar; Day, Victor W.; Berrie, Cindy L.; Thompson, Ward H.; Barybin, Mikhail V. (Inorganic Chemistry, 2008)
A one-pot transformation of bis(2-isocyano-3-methylphenyl)ethane affords gram quantities of 8,16,24,32-tetraisocyano[2.2.2.2]metacyclophane ( 3). The solid state structure of 3 is remarkably close to the lowest energy conformation found on the potential energy landscape for 3 by DFT. In solution, the structure of metacyclophane 3 is mobile but can be locked in a rectangular gauche- anti- gauche- anti conformation by coordination of the isocyanide substituents to the [W(CO) 5] units to give [M] 4(mu 4-eta (1):eta (1):eta (1):eta (1)- 3) ( 5). The tetranuclear [M] 4(mu 4-eta (1):eta (1):eta (1):eta (1)- 3) motif featured in crystallographically characterized 5 may be present in several insoluble complexes of 3 previously described as mononuclear eta (4) species. A self-assembled monolayer of metacyclophane 3 is formed upon exposing a solution of 3 to the gold(111) surface with no precautions to exclude air or light. The monolayer nature of the film was confirmed by optical ellipsometry. The isocyanide stretching band for 3 shifts from 2119 cm (-1) in solution to 2175 cm (-1) upon chemisorption to metallic gold. The FTIR spectrum of the film indicates interaction of 3 with the gold surface via all four of its isocyanide anchors. No gold-facilitated oxidation of the -NC junctions was detected under ambient conditions. The energy cost associated with accessing the conformations of 3 suitable for mu 4-eta (1):eta (1):eta (1):eta (1) interaction of the molecule with the Au(111) surface is under 8 kcal/mol, a value that can be easily offset by formation of a gold-isocyanide bond. Two different mu 4-eta (1):eta (1):eta (1):eta (1) coordination arrangements of 3 with respect to gold atoms on the (111) face of the fcc Au lattice are suggested.

Metal or nonmetal cooperation with a phenyl group: route to catalysis? a computational investigation - Ghatak, Kamalika; Mane, Manoj; Vanka, Kumar (ACS Catalysis, 2013)
Full quantum mechanical calculations demonstrate that cooperativity in the form of the activation of the M-C bond (M: transition metal or boron, C: the ipso carbon of the coordinated phenyl group) can lead to effective catalysis pathways. Calculations show that the presence of an aromatic bidentate ligand attached to a transition metal, or even a main group element, such as boron, can lead to effective catalysts for,a, range of important reactions, such as the dehydrogenation of ammonia borane and formic acid and the activation of the N-H, bond in aromatic amities. Moreover, it is shown that the design of tridentate pincer complexes with the aromatic group at a terminal end can lead to effective M-C cooperativity. As such, the current work introduces a new concept in cooperativity and bond activation chemistry.
Keywords: catalysis; Density functional theory; metal-ligand cooperativity; small molecule activation

Mechanism of oxygen atom transfer from Fe-V(O) to olefins at room temperature - Singh, Kundan K.; Tiwari, Mrityunjay K.; Dhar, Basab B.; Vanka, Kumar; Sen Gupta, Sayam (Inorganic Chemistry, 2015)
In biological oxidations, the intermediate Fe-V(0)(OH) has been proposed to be the active species for catalyzing the epoxidation of alkenes by nonheme iron complexes. However, no study has been reported yet that elucidates the mechanism of direct O-atom transfer during the reaction of Fe-V(0) with alkenes to form the corresponding epoxide. For the first time, we study the mechanism of O-atom transfer to alkenes using the Fe-V(0) complex of biuret-modified Fe-TAML at room temperature. The second-order rate constant (k(2)) for the reaction of different alkenes with Fe-V(0) was determined under single-turnover conditions. An 8000-fold rate difference was found between electron-rich (4-methoxystyrene; k(2) = 216 M-1 s(-1)) and electron-deficient (methyl transcinnamate; k(2) = 0.03 M-1 s(-1)) substrates. This rate difference indicates the electrophilic character of Fe-V(0). The use of cis-stilbene as a mechanistic probe leads to the formation of both cis- and trans-stilbene epoxides (73:27). This suggests the formation of a radical intermediate, which would allow C-C bond rotation to yield both stereoisomers of stilbene-epoxide. Additionally, a Hammett rho value of -0.56 was obtained for the para-substituted styrene derivatives. Detailed DFT calculations show that the reaction proceeds via a two-step process through a doublet spin surface. Finally, using biuret-modified Fe-TAML as the catalyst and NaOCl as the oxidant under catalytic conditions epoxide was formed with modest yields and turnover numbers.

Mechanistic insights into pincer-ligated palladium-catalyzed arylation of azoles with aryl Iodides: evidence of a Pd-II-Pd-IV-Pd-II pathway - Khake, Shrikant M.; Jagtap, Rahul A.; Dangat, Yuvraj B.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2016)
Pincer-based (R2POCNR′2)PdCl complexes along with CuI cocatalyst catalyze the arylation of azoles with aryl iodides to give the 2-arylated azole products. Herein, we report an extensive mechanistic investigation for the direct arylation of azoles involving a well-defined and highly efficient (iPr2POCNEt2)PdCl (2a) catalyst, which emphasizes a rare PdII–PdIV–PdII redox catalytic pathway. Kinetic studies and deuterium labeling experiments indicate that the C–H bond cleavage on azoles occurs via two distinct routes in a reversible manner. Controlled reactivity of the catalyst 2a underlines the iodo derivative (iPr2POCNEt2)PdI (3a) to be the resting state of the catalyst. The intermediate species (iPr2POCNEt2)Pd-benzothiazolyl (4a) has been isolated and structurally characterized. A determination of reaction rates of compound 4a with electronically different aryl iodides has revealed the kinetic significance of the oxidative addition of the C(sp2)–X electrophile, aryl iodide, to complex 4a. Furthermore, the reactivity behavior of 4a suggests that the arylation of benzothiazole proceeds via an oxidative addition/reductive elimination pathway involving a (iPr2POCNEt2)PdIV(benzothiazolyl)(Ar)I species, which is strongly supported by DFT calculations.

Mixed-stack charge transfer crystals of pillar[5]quinone and tetrathiafulvalene exhibiting ferroelectric features - Shivakumar, Kilingaru I.; Swathi, Kadaba; Goudappagouda; Das, Tamal C.; Kumar, Ashwani; Makde, Ravindra D.; Vanka, Kumar; Narayan, Kavassery S.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemistry- A European Journal, 2017)
Ferroelectric materials find extensive applications in the fabrication of compact memory devices and ultra-sensitive multifunctional detectors. Face-to-face alternate stacking of electron donors and acceptors effectuate long-range unidirectional ordering of charge-transfer (CT) dipoles, promising tunable ferroelectricity. Herein we report a new TTF-quinone system-an emerald green CT complex consisting pillar[5]quinone (P5Q) and tetrathiafulvalene (TTF). The CT crystals, as determined by single crystal synchrotron X-ray diffraction, adopt a 1:1 mixed-stack arrangement of donor and acceptor with alternating dimers of TTF and 1,4-dioxane encapsulated P5Q. The TTF-P5Q.dioxane crystal possesses a macroscopic polarization axis giving rise to ferroelectricity at room temperature. The CT complex manifests ferroelectric features such as optical polarization rotation, temperature-dependent phase transition and piezoelectric response in single crystals. Ferroelectric behavior observed in P5Q-based CT complex widens the scope for further work on this structurally intriguing and readily accessible cyclic pentaquinone.
Keywords: Acceptor; Charge-transfer complexes; Chemistry; Conductors; DDQ; Donor; ferroelectric; Macrocycles; Organic Metals; Pi-interaction; Pillar[5]quinone; salts; Transfer Complexes; Transport

Molecular motifs for additives that retard PEO crystallization - Shrivastava, Sudhakar Dinesh; Eldho, Kavalakal Mathai; Rajamohanan, P. R.; Ajithkumar, Thalasseril G.; Vanka, Kumar; Kumaraswamy, Guruswamy (Polymer Engineering & Science, 2017)
We investigate the influence of several bifunctional phenol additives (resorcinol: RES, hydroquinone: HYD, p-hydroxybenzoic acid: PHBA, and p-nitrophenol: PNP) on the crystallization of matrix polymer, polyethyleneoxide. We employ solid state Nuclear Magnetic Resonance spectroscopy (NMR), Differential Scanning Calorimetry (DSC), optical microscopy, and Small Angle X-ray Scattering (SAXS) to investigate crystallization of the additivated PEO and compare with Density Functional Theory (DFT) calculations of additive-PEO interactions. Additive-polymer interactions are a function of the functional groups on the additive. Temperature-dependent spherulitic growth rate measurements from optical microscopy and SAXS lamellar long spacings indicate a distinct trend in the effect of additives on PEO crystallization. Change in PEO crystallization is most pronounced with PNP, followed by PHBA and finally RES and HYD. This trend correlates qualitatively with the binding energies of additive-PEO interactions from DFT studies. Our results suggest that DFT calculations might be a useful screening tool to evaluate the influence of additives on polymer crystallization. POLYM. ENG. SCI., 2016. © 2016 Society of Plastics Engineers

Mechanism of nickel(II)-catalyzed C(2)-H alkynylation of indoles with alkynyl bromide - Khake, Shrikant M.; Jain, Shailja; Patel, Ulhas N.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2018)
The nickel system (THF)(2)NiBr2/phen has recently been shown as an efficient catalyst for the C-H bond alkynylation of diverse heteroarenes with (triisopropylsilyl)alkynyl bromide via monodentate chelation assistance. Herein, we report an extensive mechanistic investigation for the direct alkynylation of indoles involving the well-defined nickel catalyst, which features a coordinative insertion pathway of alkynyl bromide with the Ni(II) catalyst. Catalytic relevant nickel complexes, (phen)NiCl2 (5), (phen)(2)NiCl2 (6) and [(phen)(3)Ni].NiCl4 (7) were isolated, and the complexes 6 and 7 were structurally characterized. Well-defined complexes were as competent as the in situ generated catalyst system (THF)(2)NiBr2/phen for the alkynylation of indoles. Various controlled studies and reactivity experiments were performed to understand the probable pathway for the alkynylation reaction. Kinetics analysis highlights that the complex (phen)NiX2 acts as a precatalyst, and the involvement of substrate indole and LiO'Bu are essential for the generation of the active catalyst. Deuterium labeling and kinetic studies suggest that the process involving C-H cleavage and carbo-nickelation of indole is a crucial rate influencing step. Reactivity study of various alkynyl compounds with nickel-species highlights a migratory insertion route for the reaction. DFT calculations firmly support the experimental findings and suggest the coordinative insertion pathway of alkynyl bromide rather than oxidative addition toward the nickel(II) center.

Mechanistic aspects of pincer nickel(II)-catalyzed C-H bond alkylation of azoles with alkyl halides - Patel, Ulhas N.; Jain, Shailja; Pandey, Dilip K.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2018)
The quinolinyl-based pincer nickel complex, kappa(N),kappa(N),kappa(N)-{C9H6N-(mu-N)-C6H4-NMe2}NiCl [((NNNMe2)-N-Q)-NiCl; (1)] has recently been demonstrated to be an efficient and robust catalyst for the alkylation of azoles with alkyl halides under copper-free conditions. Herein, we report the detailed mechanistic investigation for the alkylation of azoles catalyzed by ((NNNMe2)-N-Q)NiCl (1), which highlights an iodine atom transfer (IAT) mechanism for the reaction involving a Ni-II/Ni-III process. Deuterium labeling experiments indicate reversible cleavage of the benzothiazole C-H bond, and kinetic studies underline a fractional negative rate order with the substrate benzothiazole. The involvement of an alkyl radical during the alkylation is validated by radical clock and external additive experiments. An active intermediate species ((NNNMe2)-N-Q)Ni(benzothiazolyl) (5a) has been isolated and structurally characterized. The complex ((NNNMe2)-N-Q)Ni(benzothiazoly1) (5a) is found to be the resting state of catalyst 1. Kinetic analysis of electronically different intermediates suggests that the step involving the reaction of 5a with alkyl iodide is crucial and a rate-influencing step. DFT calculations strongly support the experimental findings and corroborate an IAT process for the alkylation reaction.

Mechano-responsive room temperature luminescence variations of boron conjugated pyrene in air - Wakchaure, Vivek C.; Ranjeesh, Kayaramkodath C.; Goudappagouda; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh; Babu, Sukumaran S. (Chemical Communications, 2018)
Stimuli responsive tunable luminescence is a promising field of research. Even though mechanofluorescence is widely studied, mechanophosphorescence remains unexplored. Here we report the mechano-driven fluorescence and phosphorescence variations of a pyrene tetraboronic ester derivative. The fluorochromic and room temperature phosphorescence features are supported by theoretical studies and single crystal analysis. The mechanically ground fluorescence active but phosphorescence inactive pyrene tetraboronic ester exhibits room temperature phosphorescence in air withmechanical force. The efficient intermolecular electronic coupling in the dimer formed upon scratching enables a good communication between singlet and triplet states, hence resulting in room temperature mechanophosphorescence.

Metal-free regioselective cross dehydrogenative coupling of cyclic ethers and aryl carbonyls - Mane, Kishor D.; Mukherjee, Anagh; Vanka, Kumar; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2019)
A highly regioselective, efficient, and metal-free oxidative cross dehydrogenative coupling (CDC) of aryl carbonyls with cyclic ethers has been developed. This method offers easy access to substituted alpha-arylated cyclic ethers with a high functional group tolerance in good to excellent yields. The regioselectivity of this CDC reaction was confirmed by density functional theory (DFT)-based calculations.

Mechanistically guided one pot synthesis of phosphine-phosphite and its implication in asymmetric hydrogenation - Sen, Anirban; Kumar, Rohit; Pandey, Swechchha; Raj, K. Vipin; Kumar, Pawan; Vanka, Kumar; Chikkali, Samir H. (European Journal of Organic Chemistry, 2022)
Although hybrid bidentate ligands are known to yield highly enantioselective products in asymmetric hydrogenation (AH), synthesis of these ligands is an arduous process. Herein, a one pot, atom-economic synthesis of a hybrid phosphine-phosphite (L1) is reported. After understanding the reactivity difference between an 0-nucleophile versus C-nucleophile, one pot synthesis of Senphos (L1) was achieved (72%). When L1 was treated with [Rh], P-31 NMR revealed bidentate coordination to Rh. Senphos, in the presence of rhodium, catalyzes the AH of Methyl-2-acetamido-3-phenylacrylate and discloses an unprecedented turn over frequency of 2289, along with excellent enantio-selectivity (92%). The generality is demonstrated by hydrogenating an array of alkenes. The AH operates under mild conditions of 1-2 bar H-2 pressure, at room temperature. The practical relevance of Ll is demonstrated by scaling-up the reaction to 1 g and by synthesizing DOPA, a drug widely employed for the treatment of Parkinson's disease. Computational insights indicate that the R isomer is preferred by 3.8 kcal/mol over the S isomer.
Keywords: asymmetric hydrogenation; catalysis; DOPA synthesis; One pot synthesis; Phosphine-phosphite ligand

Magnesium-catalyzed primary, secondary, and tertiary amide hydroboration - Mahata, Biplab; Devaraj, V.; Dash, Soumya Ranjan; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2025)
Catalytic hydroboration of amides is highly important because the resultant amines are commonly found in natural products, pharmaceuticals, agrochemicals, dyes, and other applications. In comparison to the conventional reduction of amides using (over)stoichiometric reductants, hydroboration of amides using magnesium compounds represents a green and sustainable approach because magnesium is both Earth abundant and environmentally benign. However, there is only one report on magnesium-catalyzed deoxygenative hydroboration of secondary and tertiary amides. Here, we describe the synthesis and structural authentication of two new magnesium compounds (1 and 2) featuring a flexible PNP ligand and the utilization of 2 as a catalyst for the pinacolborane-mediated reduction of primary, secondary, and tertiary amides to amines. The reaction scope is explored, and a mechanism is proposed based on experimental and theoretical insights.

Magnesium-ligand cooperation in breaking the O-H and C-H bonds of water and diazoalkane - Sharma, Vishal; Dash, Soumya Ranjan; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2025)
In our previous paper, we reported that the reaction of a tridentate nacnac ligand with a pendant picolyl group, with KHMDS and MgI2, resulted in the formation of a homoleptic hexacoordinate magnesium compound. Here, we show that the analogous reaction of the ligand with CH3MgBr led to a heteroleptic magnesium bromide species (1). Attempts to generate the magnesium hydride species from 1 led to the dearomatization of the pyridine ring, and the resulting product was a magnesium hydroxide (3) presumably generated due to an adventitious amount of water. The reaction of the ligand with nBu2Mg afforded a unique dearomatized magnesium species (2) in high yield. Theoretical calculations reveal the presence of a nonbonding orbital on the magnesium, susceptible to nucleophilic attack. Indeed, the reaction of 2 with H2O/D2O cleaves the O-H/D bond via magnesium-ligand cooperation and generates a magnesium hydroxide (4 and 5). In addition, 2 reacts with Me3SiCHN2 and cleaves the C-H bond to generate another unusual, well-defined magnesium compound with a bridging isocyanide moiety (6) via migration of the SiMe3 group from the carbon to the nitrogen atom. The latter can be described as a dimer of magnesium isocyanamide. DFT calculations were performed to understand the electronic structures of the synthesized molecules.

Manganese(i)-catalyzed dehydrogenative borylation of terminal alkynes - Ghanwat, Pratiksha B.; Bora, Debashree; Pandya, Rinu; Vanka, Kumar; Saha, Biswajit; Sen, Sakya S. (Dalton Transactions, 2025)
Compounds containing carbon-boron bonds serve as valuable intermediates for constructing more complex molecules by transforming these bonds into other carbon-element bonds. The catalytic dehydrogenative borylation of carbon-hydrogen bonds using HBpin presents an appealing method for synthesizing carbon-boron bonds. While this approach has been extensively explored with noble metals for various types of carbon-hydrogen bonds, its application with manganese-based catalysts remains rare. This study explores a dehydrogenative borylation process employing an Earth-abundant transition metal catalyst, FcbpyMn(CO)3Br (Mn(i)), in combination with HBpin under mild conditions. Arylalkynes featuring electron-withdrawing, electron-donating, and heteroaryl substituents yielded good to excellent results. Thorough DFT calculations were performed to understand the mechanism.